A New Technological Approach to Money Laundering Discovery Using Analytical SQL Server - Korczak, Jerzy; Merchelski, Wojciech; Oleszkiewicz, Błażej (Advanced Information Technologies for Management – AITM 2008, 2008)
In the paper a new idea of system architecture for money laundering discovery is presented. The considerations relate to the software platform, called SART Analytical SQL Server, that was used to build complete anti-money laundering (AML) applications. This software platform is based on the data warehouse technology and contains advanced analytical functions, OLAP and data mining methods. Architecture and main functionalities of the SART system have been demonstrated using data coming from a bank information system. Our study will demonstrate how to build data warehouse structures to identify suspicious transactions and objects, based on the concepts of multi- dimensional, heterogenic ROLAP cubes and transaction chains. In conclusion, the advantages of the proposed solution are summed up in the context of new trends in OLAP as well as in Business Intelligence research and development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 86-104